2012
DOI: 10.1103/physrevc.85.015202
|View full text |Cite
|
Sign up to set email alerts
|

Semi-inclusive charged-pion electroproduction off protons and deuterons: Cross sections, ratios, and access to the quark-parton model at low energies

Abstract: A large set of cross sections for semi-inclusive electroproduction of charged pions (π ± ) from both proton and deuteron targets was measured. The data are in the deep-inelastic scattering region with invariant mass squared W 2 > 4 GeV 2 (up to ≈ 7 GeV 2 ) and range in four-momentum transfer squared 2 < Q 2 < 4 (GeV/c) 2 , and cover a range in the Bjorken scaling variable 0.2 < x < 0.6. The fractional energy of the pions spans a range 0.3 < z < 1, with small transverse momenta with respect to the virtual-photo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 126 publications
2
27
0
Order By: Relevance
“…In any case, we remark that the average kinematics of the experiment taken into consideration in Refs. [24,26] are different from Hermes (see also the discussion in Ref. [58]).…”
Section: Fit With Pions Onlymentioning
confidence: 97%
See 1 more Smart Citation
“…In any case, we remark that the average kinematics of the experiment taken into consideration in Refs. [24,26] are different from Hermes (see also the discussion in Ref. [58]).…”
Section: Fit With Pions Onlymentioning
confidence: 97%
“…This is a landmark achievement in the knowledge of the internal structure of hadrons. Earlier data already gave some indications, but were limited in the variety of targets, or final-state hadrons, or multidimensional coverage (see, e.g., [22][23][24][25][26]). The Compass collaboration has recently released similar data [27].…”
mentioning
confidence: 99%
“…In Figure 14, the h þ multiplicities are compared to the π þ semi-inclusive cross section measured by the E00-18 experiment [31] at Jefferson Lab. The measurement by the E00-18 was performed at hzi ¼ 0.55 and hxi ¼ 0.32 in the range 2 ðGeV=cÞ 2 < Q 2 < 4 ðGeV=cÞ 2 .…”
Section: B Comparison With Other Measurementsmentioning
confidence: 99%
“…While it has been shown that the evolution effect is expected to be significant, most of the existing studies used the simple formalism (GPM) described in section 2. While factorization originates in the high energy limit (Q Λ QCD or Q M nucleon ) [12,60], and at low Q 2 the description with hadronic degrees of freedom is more widely used [28], the applicability of the quark-parton model with factorization in the modest Q 2 ranges has been observed in the quark-hadron duality [64,65].…”
Section: Experiments and Phenomenology Of Tmdmentioning
confidence: 99%